If this is indoctrination, we are all indoctrinated. (November 2022) - Armstrong, Luke
When thinking about moral education, a concern of liberals is that such education ought not to be indoctrinatory. There are various definitions of indoctrination, but a common theme is that indoctrination prevents us from critically assessing our own beliefs. Indoctrinatory education, then, teaches a doctrine in such a way that students will not countenance any alternative doctrines. A state which forced its citizens to endorse a doctrine in this way would not be a liberal state. However, if indoctrination consists in an inability to critically assess our own beliefs, I argue that we are all partly indoctrinated. Evidence drawn from neuroscience and psychology suggests that the basis of our beliefs lies in emotion rather than reason, and there is no independent space from which we can critically assess our own belief systems. This is not to justify an explicit form of state indoctrination, in which the state forces beliefs upon us. Instead, it is to assess problems with how we understand indoctrination within education. There is no entirely adequate solution to these problems, though education aimed at open-mindedness offers the most promise.